CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

To eliminate y from the equations 3x - 2y $$=$$ 1 and 5x + y $$=$$ 6, the second equation should be multiplied by -


A
1
loader
B
2
loader
C
3
loader
D
4
loader

Solution

The correct option is B 2
Multiply the second equation by 2 and add equation 1.

$$ 10x+2y=12$$ and $$3x-2y=1$$

Adding both

$$13x=13$$

$$\therefore x = 1\ and\ y=1 $$

Mathematics

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More


similar_icon
People also searched for
View More



footer-image